Indocyanine green can stand alone in detecting sentinel lymph nodes in cervical cancer - Ulain, Qurat (J Int Med Res, 2018)
OBJECTIVES: The effectiveness of indocyanine green (ICG) dye for detecting sentinel lymph nodes (SLNs) in cervical cancer compared with other tracers is unknown. This study aimed to assess the validity of ICG dye in detecting SLNs in cervical cancer preoperatively. METHODS: We performed a literature search for identifying eligible articles from PubMed database using the search terms “cervical cancer”, “sentinel lymph node”, “indocyanine green”, “blue dyes”, “human serum albumin”, and “technetium-99 radiocolloid”. We performed a meta-analysis. Comparison of the overall, bilateral, and unilateral detection rates of the different tracers was the primary goal. Comparison of the false-negative rate among the tracers was the secondary goal. RESULTS: Only eight retrospective studies including 661 patients were included. ICG versus combinations of three other tracers showed significantly higher bilateral and unilateral detection rates, but no difference in the overall rate of detecting SLNs. ICG had a higher bilateral detection rate than blue dye and technetium-99. Absorbing human serum albumin into ICG as a lymphatic tracer did not show a difference in detection rate compared with ICG alone. CONCLUSIONS: ICG is superior and better than other tracers, and absorbing human serum albumin as a lymphatic tracer is not required in patients with cervical cancer.